ANALISIS KUALITAS PELAYANAN PUBLIK DI DESA KARANGGEGER KECAMATAN PAJARAKAN KABUPATEN PROBOLINGGO - Aris Subekti; Sunairi Hariyanto (LP2M Universitas Bina Bangsa, 2022)
Public service or service to the community is an important element that can be used as an indication of the success of government leadership. Similarly, the national reform movement, which does not mean anything if the service to the public mash is less feasible. In addition, to create